The paper menagerie and other stories ebook - Liu, Ken (2015)
Featured in the Netflix series Love, Death & Robots Bestselling author Ken Liu selects his multiple award-winning stories for a groundbreaking collection—including a brand-new piece exclusive to this volume. With his debut novel, The Grace of Kings , taking the literary world by storm, Ken Liu now shares his finest short fiction in The Paper Menagerie and Other Stories . This mesmerizing collection features many of Ken's award-winning and award-finalist stories, including: "The Man Who Ended History: A Documentary" (Finalist for the Hugo, Nebula, and Theodore Sturgeon Awards), "Mono No Aware" (Hugo Award winner), "The Waves" (Nebula Award finalist), "The Bookmaking Habits of Select Species" (Nebula and Sturgeon Award finalists), "All the Flavors" (Nebula Award finalist), "The Litigation Master and the Monkey King" (Nebula Award finalist), and the most awarded story in the genre's history, "The Paper Menagerie" (The only story to win the Hugo, Nebula, and World Fantasy awards). Insightful and stunning stories that plumb the struggle against history and betrayal of relationships in pivotal moments, this collection showcases one of our greatest and original voices.